The Function of Macronutrients in Helping Soybeans to Overcome the Negative Effects of Drought Stress - Staniak, Mariola; Szpunar-Krok, Ewa; Wilczewski, Edward; Kocira, Anna; Podleśny, Janusz (Agronomy (Basel), 2024)
Nutrient deficiencies are a major cause of yield loss under abiotic stress conditions, so proper nutrient management can reduce the negative effects of stress to some extent. Nutrients can alleviate stress by activating resistance genes, enhancing antioxidant enzyme activity, creating osmoprotectants in cells, reducing reactive oxygen species (ROS) activity, increasing cell membrane stability, synthesizing proteins associated with stress tolerance, and increasing chlorophyll content in leaves. The current review highlights changes in soybean metabolic activity caused by drought stress and changes in vital functions caused by the deficiency of primary (N, K, P) and secondary macronutrients (Ca, Mg, S). The role of macronutrients in reducing the adverse effects of water deficit stress is highlighted. Under stressed conditions, appropriate nutrient management options can be implemented to minimize the effects of drought and ensure good yields. Balanced nutrient fertilization helps activate various plant mechanisms to mitigate the effects of abiotic stresses and improve soybean drought resistance/tolerance. Nutrient management is therefore a viable technique for reducing environmental stress and increasing crop productivity.